Comparison of MRCP and ERCP in the evaluation of common bile duct and pancreatic duct pathologies - Kumar, Anand; Mohanty, Nihar Ranjan; Mohanty, Madhusmita; Dash, Sashibhusan (Frontiers in Medical Technology, 2023)
Background: Magnetic resonance cholangiography (MRCP) is a noninvasive imaging modality that has high diagnostic accuracy for a wide range of bile duct and pancreatic duct pathologies. Endoscopic retrograde cholangiopancreatography (ERCP) is still the gold standard for the exploration of the biliopancreatic region. Aim: To compare the diagnostic accuracy of magnetic resonance cholangiography with that of endoscopic retrograde cholangiopancreatography in the diagnosis of the bile duct and pancreatic duct pathologies. Material and methods: Sixty patients with CBD and pancreatic duct pathologies detected on MRCP were subsequently evaluated by ERCP in this observational study. A comparison of MRCP findings was done with ERCP which is the gold standard. Results: MRCP had sensitivity, specificity, positive predictive value (PPV), negative predictive value ( NPV), and accuracy of 88.1%, 94.4%, 97.3%, 72.7%, and 90% respectively in diagnosing choledocholithiasis in comparison to ERCP. For CBD dilation the sensitivity 90.91%, specificity was 93.75%,the PPV,NPV and accuracy were 97.56%, 78.95% and 91.67% respectively for MRCP. In CBD stricture MRCP showed sensitivity, specificity, PPV, NPV and accuracy of 83.33%, 97.92%, 90.91%, 95.92% and 95% respectively. In pancreatic duct dilatation sensitivity, specificity, PPV, NPVand accuracy were all 100%. Pancreatic duct stricture showed 80%, 98%, 88.89%, 96.08% and 95% for sensitivity, specificity, PPV, NPV and accuracy respectively. For diagnosis of periampullary neoplasm sensitivity, specificity, PPV, NPV, and accuracy rate of MRCP were 80%, 98%, 88.89%, 96.08%, and 95% respectively. There is no significant difference in the evaluation of pathologies by MRCP and ERCP (p=<0.00001) Conclusion: MRCP, with reference to ERCP has no significant difference in diagnosing those six pathologies.